1992
DOI: 10.1161/01.cir.86.5.1495
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and urinary excretion of thromboxane A2 and prostacyclin metabolites in women stratified by age.

Abstract: Background. Activated platelets have been implicated in both acute thrombus formation and atherogenesis. Because smoking is a risk factor for cardiovascular disease in men and women and male smokers have biochemical evidence of increased platelet activation, we found it of interest to study whether smoking augments platelet activity in women as well.Methods and Results. Data on smoking habits and a urinary sample were obtained from 125 healthy female nonsmokers and an equal number of smokers, stratified by age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
4
24
1
1
Order By: Relevance
“…75 ) Smith and colleagues 85 concluded that SHS exposure levels did not activate platelets in "typical home environments" because no difference in urinary thromboxane and prostacyclin was observed between nonsmokers from nonsmoking homes and nonsmokers from smoking homes. However, Smith's smoker "control group" did not demonstrate significantly elevated thromboxane relative to the 2 nonsmoker groups, which contradicted previous tobacco industry-funded literature 94,95 demonstrating that active smoking was associated with thromboxane release. In the discussion, Smith and his coauthors acknowledged this inconsistency but argued that the active smokers in the study reacted differently because of large smoke exposures.…”
Section: Attacking Biological Plausibility: Rjr Experimentscontrasting
confidence: 63%
See 2 more Smart Citations
“…75 ) Smith and colleagues 85 concluded that SHS exposure levels did not activate platelets in "typical home environments" because no difference in urinary thromboxane and prostacyclin was observed between nonsmokers from nonsmoking homes and nonsmokers from smoking homes. However, Smith's smoker "control group" did not demonstrate significantly elevated thromboxane relative to the 2 nonsmoker groups, which contradicted previous tobacco industry-funded literature 94,95 demonstrating that active smoking was associated with thromboxane release. In the discussion, Smith and his coauthors acknowledged this inconsistency but argued that the active smokers in the study reacted differently because of large smoke exposures.…”
Section: Attacking Biological Plausibility: Rjr Experimentscontrasting
confidence: 63%
“…104 Reviewers 125 of the manuscript for Toxicological Sciences questioned the variation in the thromboxane levels because the nonsmokers not exposed to SHS had a higher level of urinary thromboxane than the nonsmokers exposed to SHS. In the final published article, 91 Smith acknowledged that these results were not consistent with previous literature 94,95 suggesting that thromboxane was released with active smoking but suggested that the higher levels were due to an unknown stress (although Smith did not find that oxidative or hormonal stress was significantly associated). Reviewers 125 also noted a failure to comment on other relevant literature such as the 1996 human exposure experiment 106 that demonstrated that repeated daily exposures to SHS over 1 week elevated nonsmoker levels of serum thromboxane to those comparable to active smokers; this literature was not addressed in Smith's final publication.…”
Section: Testing the Hormonal And Oxidative Stress Hypothesismentioning
confidence: 69%
See 1 more Smart Citation
“…15 Similar signs of a reversible effect of smoking on Tx-M excretion were recently obtained in a study on smoking and nonsmoking women aged 18-59 years. 27 Controlled studies on the change in Tx-M excretion immediately after cessation of smoking have, however, not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…27 In that study former smokers did not differ from lifelong nonsmokers in excretion of Tx-M. To further characterize the apparent reversibility in the effect of smoking, we followed urinary excretion of the TxA 2 metabolites Tx-M and ll-dehydro-TxBj (dTx) 2829 in women who were quitting habitual smoking. We also determined the urinary excretion of 2,3-dinor-6-keto-prostaglandin F lo (PGI-M), a metabolite of prostacyclin, 30 ' 31 since it has been proposed that an increased formation of prostacyclin in the vascular endothelium may reflect an increased interaction between the platelets and the vascular endothelium.…”
mentioning
confidence: 94%